2008
DOI: 10.3139/146.101669
|View full text |Cite
|
Sign up to set email alerts
|

Properties of hydrogen absorption by nano-structured FeTi alloys

Abstract: In this study, two different nano-structured samples of the FeTi compound were prepared by mechanical alloying and mechanical grinding. For these samples, kinetics of the initial rate of hydrogen absorption, and the equilibrium hydrogen pressure as a function of hydrogen concentration were measured. Mechanical alloying of Fe and Ti atoms produced the FeTi compound powder samples with microstructures of a mixture of nano-structured FeTi grains and amorphous phases. This sample exhibited a high initial rate of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…For example, it was also reported that FeTi alloys undergo hydrogen capacity loss after milling process. This is due to the creation of amorphous regions induced by the mechanical deformation and it is not possible to store hydrogen interstitially in the amorphous regions [65]. Furthermore, taking into account that the milling vessel and grinding medium are usually made of stainless steel, Fe contamination is also a concern, particularly at the time to perform the milling process in a highenergy mill device.…”
Section: Mechanical Millingmentioning
confidence: 99%
“…For example, it was also reported that FeTi alloys undergo hydrogen capacity loss after milling process. This is due to the creation of amorphous regions induced by the mechanical deformation and it is not possible to store hydrogen interstitially in the amorphous regions [65]. Furthermore, taking into account that the milling vessel and grinding medium are usually made of stainless steel, Fe contamination is also a concern, particularly at the time to perform the milling process in a highenergy mill device.…”
Section: Mechanical Millingmentioning
confidence: 99%
“…Für den Transport und das Speichern von H 2 innerhalb Japans untersuchen japanische Forscher außer Hydriden nanostrukturierte Fe-Ti-Legierungen, die Wasserstoff re-versibel binden. 10) Sie dienen bereits zur Temperaturkontrolle in Gewächshäusern und in der Aquakultur.…”
Section: Wasserstoffbetrieben Fahrenunclassified
“…[4][5][6] In 1974, the first successful results on hydrogen storage in TiFe at room temperature were reported by Reilly and Wiswall, but they found that the as-cast material should be activated by repeated exposure to vacuum and hydrogen atmosphere at temperatures as high as 673 K. [4] Later studies also showed that despite all advantages of TiFe, its difficult activation is a main drawback. [7][8][9][10] There have been several attempts to solve the activation problem of as-cast TiFe mainly using two strategies: 1) chemical activation by addition of a third element, such as Pd, [11] Ni, [12] Mn, [13][14][15][16] and Zr [17][18][19] and 2) mechanical activation by ball milling, [20][21][22] high-pressure torsion (HPT), [23][24][25] and cold rolling. [26,27] Although the exact mechanism for the activation of TiFe is still under argument, it is generally believed that the first strategy is based on the surface catalytic performance of elemental additives, and the second strategy is based on nanostructuring and introduction of hydrogen pathways into bulk, such as cracks, nanograin boundaries, and amorphous regions.…”
Section: Introductionmentioning
confidence: 99%